Estudo de filmes de poli(ácido lático) obtidos por fiação por sopro em solução reforçados com nanocristais de celulose - Parize, Delne Domingos da Silva (2016)
Solution blow spinning is a technique to produce micro- and nano-scale fibers, forming films with high porosity and surface area. Chemical modifications or the incorporation of nanostructures in these fibers can improve the performance of these films for various applications, such as membranes, tissue engineering and sensors. Therefore, the aim of this work was to study poly(lactic acid) (PLA) films obtained by solution blow spinning reinforced with cellulose nanocrystals (CNC). First, different solvents were evaluated in order to determine the best processing conditions and the feasibility of using the solvent dimethyl carbonate (DMC) in the production of PLA films by solution blow spinning. Polymer concentration showed to be the most significant parameter affecting fiber diameter and DMC presented advantages over 1,1,1,3,3,3-hexafluoro-2-propanol (HFP) and chloroform due its less toxicity, and therefore, is an alternative solvent with an affordable price, using a more environmentally-friendly process. Subsequently, the CNCs were extracted from bleached eucalyptus kraft pulp by sulfuric acid hydrolysis, which were chemically modified with maleic anhydride (CNCMA). Then, composite films of PLA/CNC and PLA/CNCMA were obtained by solution blow spinning and the results indicated that the addition of nanocrystals did not significantly affected fiber diameters, although the fiber diameters tended to decrease with the increase of the nanocrystals concentration. The results also indicated that the nanocrystals may have increased the degree of PLA polymer chains orientation and that the composite films presented a more hydrophilic behavior when compared to the pure PLA film. It suggests that some of the nanocrystals may be on the surface of the fibers, indicating that these composite films are promising for filter and adsorbents membranes application.